New Design of Objective Lens Geometry for Low Voltage SEM - M. A. Al-Khashab; R. Y. Al-Salih (Jordan Journal of Physics, 2025)
Five new models of magnetic objective lens geometry have been designed and studied in this work. Different excitation coil shapes and their positions inside the lenses at a constant excitation (NI = 10 kA.t) were included. Spacious comparison between these models was realized using the finite element method (FEM) to analyze the magnetic field distribution, magnetic flux density and opticalproperties for each model at low relativistic corrected accelerating voltage (Vr= 10 kV). The effect of the lens geometrical shape on the electron beam voltage passing throughout the optical axis of the lenses at zero image plane (Zi= 0 mm) has been inspected as well. The optimized one of the deliberated lenses has been selected as an objective lens for low voltage scanning electron microscope (SEM) preparatory for next research. Keywords: Objective lens geometry design; Electron magnetic properties; Electron optical properties; Relativistic corrected accelerating voltage; Low voltage SEM.